Culture and religion creolisation impact on digital advertisement of Muslim users of Instagram - Mirvaisi, Majid (HTS teologiese studies, 2023)
Over the last decade, digitalisation has been a subject of increasing attention among scholars and practitioners. The effect of culture and religion on advertisements, consumerism and marketing, is deniable. The main goal of this research is to present a comprehensive conceptual model based on cultural and religious diversity in digital marketing. This research mainly includes introduction creolisation concept and the elements (religion, music, clothes and custom) as the most important factor in digital advertisement and branding. In this regard, this study examines Instagram consumer products users from five different subcultures in Iran (Lor, Kurdish, Baluch, Arab and Azeri) and considers the impact of creolisation elements on digital advertising, brand identity and brand globalisation. Data were collected by sending 1200 questionnaire via email to subcultures and then analysed using LISREL software.Contribution: The results demonstrated that Islamic religion between participants affects their brand loyalty, therefore the Islamic worth in advertising is necessary. It was suggested that creolisation elements significantly affect digital advertisement, brand identity and brand globalisation. Consequently, all hypotheses were accepted. On the other hand, the impact of brand identity and digital advertisement on the brand globalisation was also confirmed. Discussion and managerial implications concerning creolisation were explained.